Assessment of dental erosion status among battery factory workers in Mandideep, India - Rohit Agrawal; Geeta Mishra Tripathi; Vrinda Saxena; Neha Singh; Vijayta Sharva; Kaluram Yadav (Occupational Health and Safety Society of Nepal, 2015)
Introduction: Occupational factors may be considered responsible for dental erosion among battery factory workers since they were exposed to sulfuric acid fumes created by the harmful processes known as forming and charging. Methods: A sample consisted of 138 battery factory workers (85 acid exposed workers and 53 controls) drawn as a convenient sample from 3 different battery factories of Mandideep, India. A pre-tested proforma, completed by interview, was used to collect information on medical and dental histories. Clinical examination of battery factory workers was done to assess dental erosion using tooth wear index given by Smith and Knight. Data related to dental erosion score of acid worker and control group was compared using Mann Whitney U test. Categorical data was analyzed by chi-square test. Results: The battery factory workers showed a propensity for higher erosion scores. The result of present survey showed a total of 74 percent of acid exposed workers had erosion compared to 37.7 percent of the controls. Statistical difference in erosion scores between acid exposed group and control group was found significant (p value<0.05). Conclusion: Present study revealed that long term exposure of sulphuric acid mists in the working environment significantly increased the chances of dental erosion among exposed workers. There is urgent need for surveillance and routine monitoring of acid fumes at workplace coupled with education about occupational hazards, positive worksite oral health promotion and training for standardized behaviors such as use of personal protective equipment to decrease occupational erosion.